Community based comparative study on disability, psychosocial aspects , healthcare seeking behaviour and morbidity control of people with chronic filarial lymphoedema in Colombo District - Samarasekara, S.D (My University, 2009)
Lymphatic filariasis, a mosquito-borne parasitic disease, can lead to lymphoedema and elephantiasis, is a major contributor to disability in the developing world. Information on the disability and psychological impact of filarial lymphoedema patients in the community in Sri Lanka are scarce. Morbidity control practices of the filarial lymphoedema (FL) patients in a community setting were not assessed after their introduction, other than assessing in the clinic setting. Therefore, this study was carried out to assess the disease status, health care seeking behavior, acute adenolymphangitis (ADL) attacks, knowledge and practices related to morbidity control among patients with filarial lymphoedema in the community and compared the patients with a matched comparison group from the community for socio demographic factors, disability, psychological distress and knowledge on filariasis. Study had three components. Component I translated the World Health Organization Disability Assessment Schedule II (WHODAS II) in to Sinhala and validated it among 180 patients with filarial lymphoedema and their comparison group (180) in the Kalutara district before its application in the main study. Even though, all the cases had ever attended at least one allopathic doctor and treated with DEC, only 57 percent of cases had ever attended a filariasis clinic and only 37 percent out of cases had visited the filariasis clinics during last 5 years after the commencement of educating the morbidity control measures in the year 2003. ADL attacks and repeated ADL attacks aggravate the swelling leading to elephantiasis. About 80 percent of cases reported of ever having ADL attacks, 35.0 percent had experienced ADL attacks during the last one year, while 17 percent had experienced ADL attacks during the past three months. A majority had warmed their limbs (80.0 percent ) during ADL attacks, which is an incorrect practice. ADL attacks during last one year, was significantly higher among those with: lower educational categories, lower income categories (p =0.007), Grade III and Grade IV lymphoedema (p=O.OOO), not wearing footwear (p~O.OOO), not practicing washing as a morbidity control measure (p -0.001), and not attending the filarisis clinic during last 5 years (p-'O.O 15). The study concluded that WHODAS II is a valid and reliable tool to assess disability among patients with filarial. Community Home Based Care (CHBC) services should be provided to ensure the patients practicing morbidity control measures. Measures should be taken to improve the psychological wellbeing of the FL patients, as it was shown by both qualitative and quantitative methods that they experience psychological distress. Counseling programmes should be implemented targeting the clinic attendees and those in the community.